Cost effective comparison between concrete and steel composite structure for 2 storeys building - Meor Airol Shafiq, Meor Shamsuddin (2012)
Cost is one of the important things to be considered in construction sector but also to other sector such as selling business. However this research more concentrated in construction sector which are fast developing in Malaysia. Day by day, material price for construction is increasing. Statistics showed many projects is interrupted due to mistake cost calculation during planning stage. Therefore it is important to understand how overall price could be influenced. Price scope involved in this research is price of material, labour wage and machinery rental cost. This research is carried out by comparing two types of building which is concrete structure and steel composite structure. The constant variable for both structures is area of the building. This thesis is to study which building material is more economical and the most influencing of overall cost based on Malaysia current trend of building structure materials. To analysis the project, two software is using which is Esteem 4.0 and Microsoft Project 2007. Other that, price calculation will be calculated manually. At the end of the research there are significant differences in the overall price that can be guide for those responsible to choose which structure actually is cost saving for the current being.